2014
DOI: 10.1016/j.molbiopara.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the small RNA content of Trypanosoma cruzi extracellular vesicles

Abstract: A growing body of evidence in mammalian cells indicates that secreted vesicles can be used to mediate intercellular communication processes by transferring various bioactive molecules, including mRNAs and microRNAs. Based on these findings, we decided to analyze whether Trypanosoma cruzi-derived extracellular vesicles contain RNA molecules and performed a deep sequencing and genome-wide analysis of a size-fractioned cDNA library (16–40 nt) from extracellular vesicles secreted by noninfective epimastigote and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 22 publications
6
57
1
1
Order By: Relevance
“…Similarly to previous results from our lab [14] and from Bayer-Santos et al [1] the proportion of small RNAs derived from rRNA and tRNA included in extracellular vesicles was about 90%. However, the relative abundance of different classes of small RNAs reported for Bayer-Santos et al showed some variations.…”
Section: Small Rnas Derived From Trnas and Rrnas Represent More Than supporting
confidence: 90%
See 1 more Smart Citation
“…Similarly to previous results from our lab [14] and from Bayer-Santos et al [1] the proportion of small RNAs derived from rRNA and tRNA included in extracellular vesicles was about 90%. However, the relative abundance of different classes of small RNAs reported for Bayer-Santos et al showed some variations.…”
Section: Small Rnas Derived From Trnas and Rrnas Represent More Than supporting
confidence: 90%
“…In this respect, Bayer-Santos and col. have recently sequenced T. cruzi small RNA from epimastigote extracellular vesicles, metacyclic extracellular vesicles and the intracellular compartment of metacyclic forms [1]. They categorized sequenced RNAs in seven categories (tRNAs, snRNAs, snoRNAs, CDS, pseudogenes and unspecified reads) and analyzed only the small RNAs derived from transfer RNAs describing the issoaceptor precursors and their quantitative contribution to the total population of tRNA halves sequenced.…”
Section: Q2mentioning
confidence: 99%
“…These include exovesicles (EVs; also referred to as ectosomes; 100 to 1,000 nm), which bud directly from the plasma membrane, and exosomes (30 to 100 nm), which are vesicles that are secreted into the extracellular environment following the fusion of multivesicular endosomes with the plasma membrane, typically occurring at the flagellar pocket membrane (28,(30)(31)(32)(33). A proteomic analysis of extracellular vesicles released by metacyclic trypomastigotes and epimastigotes in culture demonstrated the presence of two populations of EVs containing plasma membrane and intracellular proteins, and also nucleic acids (26,29,(32)(33)(34). Interestingly, treatment of mice with EVs shed by axenic trypomastigotes caused a downmodulation of the host immune response that was associated with higher parasitemia and an exacerbated inflammatory response that resulted in increased mortality following infection (26,35).…”
mentioning
confidence: 99%
“…Bayer-Santos, et al [56] recently analyzed vesicles isolated from T. cruzi epimastigotes and metacyclic trypomastigotes from the Dm28c strain. The results showed that the vesicles were composed of a wide variety of RNA molecules including rRNA, mRNAs, and small RNAs.…”
Section: Exosomes In the Protozoan Trypanosoma Cruzimentioning
confidence: 99%